Impact of board structure on corporate performance: an empirical study of listed banking & finance companies in sri lanka. - Thavarasasingam, H.; Balagobei, S.; Anandasayanan, S. (University of Jaffna, 2019)
The aim of this paper is to measure the relationship between board structure and the corporate performance of listed Banking and Finance companies listed in Colombo Stock Exchange. This study incorporated 24 firms as sample over the period 2011- 2017. To measure corporate performance Earning per share is the key variable. On the other hand board structure is measured through frequency of board meetings, board size, board independence, CEO duality and percentage of Female member of board respectively. With the help of simple least square regression this study found significant and positive relationship between board meeting and EPS and board size has a significant negative impact on EPS. It can be said that the results are mostly consistent with previous studies and suggests that board characteristics is keen to be highlighted to improve the corporate performance and to survive in the competitive market.
Keywords: Board structure; CEO duality; Board meeting; Corporate performance